Wheat consumption and prevalence of celiac disease: Correlation from a multilevel analysis. Issue 1 (2nd January 2023) - Bradauskiene, Vijole; Vaiciulyte-Funk, Lina; Martinaitiene, Dalia; Andruskiene, Jurgita; Verma, Anil K.; Lima, João P. M.; Serin, Yeliz; Catassi, Carlo
Abstract: Celiac disease (CD) is triggered by both genetic and environmental factors. More than 1% of the world's population is affected by CD. In recent years, studies have confirmed a worldwide rising trend in CD prevalence. "Westernized diet" is one of the main factors of this increasing prevalence. However, the relationship between wheat consumption, its dynamics, and CD has not been adequately investigated on a global scale. This study aimed to perform a multilevel analysis of the association between wheat consumption and CD. Wheat consumption data from countries and continents were obtained from the database. The relative increase/decrease in wheat consumption over a long period (since 1961) and a short period (since 2004) were calculated using various statistical tools. The relationship between wheat consumption and celiac frequency was determined using the R-commander R package version 2.6-2. Pearson's correlation coefficient (r = 0.88) confirmed a high positive correlation between wheat consumption and the prevalence of biopsy-proven CD by estimating continent-wide wheat consumption data, but an insignificant correlation was found when the data were compared country-wide.